Suluk Pendidikan Islam dalam Relasi Identik Rokok dan Korek Api - Robingun Suyud El Syam (Concept: Journal of Social Humanities and Education, 2023)
This study focuses on the objective of describing Islamic education in the identical relation of cigarettes and lighters, so that it is different from previous writings, and focuses on the element of novelty. The research is the result of qualitative research with a phenomenological approach setting on the relationship between cigarettes and lighters through literature reference sources, qualitatively analyzed by emphasizing the findings of meaning. The results of the research show that in Islamic education there are always pioneers who open up space for the advancement of an education. They laid a useful foundation for the robustness of further educational buildings. Therefore, never forget the services of the pioneers of education, because without them you cannot feel the progress of education in the current era. The implications of research on the importance of the process of studying the knowledge of educational pioneers are manifested enthusiastically, not in results. The research is expected to be useful for building sustainable Islamic education